Is “watch and wait” a viable option for surgically resected brain metastases? - Kang, John; Milano, Michael T. (Therapeutic Radiology and Oncology, 2018)
A Phase III Japan Clinical Oncology Group (JCOG) trial, by Kayama et al., randomized patients with ≤4 brain metastases (single brain metastasis in 73%), who underwent resection of at least one brain metastasis, to adjuvant whole brain radiotherapy (WBRT) or salvage stereotactic radiosurgery (SRS) (1).